Fear of Missing Out (FoMO) as a Psychological Challenge in Students’ Learning Process at MTs Futuhiyyah Kudu Semarang - Syafarudin (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the phenomenon of Fear of Missing Out (FoMO) as a psychological challenge in the learning process of students at MTs Futuhiyyah Kudu Semarang. The rapid development of digital technology and the intensive use of social media among adolescents have increased the tendency to remain continuously connected to online information and social activities. This condition may influence students’ learning concentration, academic engagement, and self-regulation. This research employed a qualitative approach with a case study design. The participants were eighth-grade students of MTs Futuhiyyah Kudu Semarang selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings reveal that FoMO is experienced by students due to the high intensity of social media use in their daily lives. FoMO is reflected in frequent smartphone checking, difficulty diverting attention from social media notifications, and anxiety when missing social information. These conditions affect the learning process by reducing concentration, academic engagement, and self-regulation. In the context of madrasah education, FoMO represents not only a psychological challenge but also a pedagogical issue related to character development and self-control grounded in Islamic values. Strengthening digital literacy, self-regulation, and collaboration among teachers, parents, and schools is therefore essential to promote balanced and healthy social media use